Implications of EMG channel count: enhancing pattern recognition online prosthetic testing - Simon, Ann M.; Newkirk, Keira; Miller, Laura A.; Turner, Kristi L.; Brenner, Kevin; Stephens, Michael; Hargrove, Levi J. (Frontiers in Rehabilitation Sciences, 2024)
Myoelectric pattern recognition systems have shown promising control of upper limb powered prostheses and are now commercially available. These pattern recognition systems typically record from up to 8 muscle sites, whereas other control systems use two-site control. While previous offline studies have shown 8 or fewer sites to be optimal, real-time control was not evaluated. In this study, six individuals with no limb absence and four individuals with a transradial amputation controlled a virtual upper limb prosthesis using pattern recognition control with 8 and 16 channels of EMG. Additionally, two of the individuals with a transradial amputation performed the Assessment for Capacity of Myoelectric Control (ACMC) with a multi-articulating hand and wrist prosthesis with the same channel count conditions. Results indicated significant improvements in control when using 16 compared to 8 EMG channels including decreased classification error (p=0.006), decreased completion time (p=0.019), and increased path efficiency (p=0.013) when controlling a virtual prosthesis. ACMC scores increased by more than three times the minimal detectable change from the 8 to the 16-channel condition. The results of this study indicate that increasing EMG channel count beyond the clinical standard of 8 channels can benefit myoelectric pattern recognition users.